DO CAPITAL EXPENDITURES HAVE A MODERATING EFFECT ON THE ASSOCIATION BETWEEN REGIONAL GOVERNMENT DEPENDENCE, SIZE AND FINANCIAL INFORMATION TRANSPARENCY? - Firmansyah, Amrie; Sitorus, Laurenza; Harsoyo, Allamanda Titania (IPSAR (International Public Sector Accounting Review), 2024)
This research aims to analyze the influence of dependence and size of local government on the transparency of financial information by using the proportion of capital expenditure as a moderating variable. Research was conducted in four cities and four regencies in Banten Province for five years (2018 - 2022). The method used is purposive sampling using secondary data from Regional Government financial reports and other related documents. Data was collected by accessing the official Regional Government website to search for financial information from 2018 to 2022. Hypothesis testing was carried out using multiple regression analysis for panel data. The research results show that the level of Regional Government dependency and the size of the Regional Government do not influence the transparency of Regional Government financial information, and capital expenditure does not play a moderating role in this relationship. This research implies the importance of transparency of Regional Government financial information as a monitoring medium for the community, especially in managing capital expenditure.